Pengendalian Kimia dan Ketahanan Colletotrichum spp. terhadap Fungisida Simoksanil pada Cabai Merah - NIken Rasmi Paramita (Jurnal Perlindungan Tanaman Indonesia, 2014)
Colletotrichum sp. is an important pathogen on pepper and caused losses up to 50-100% in rainy season. The objectives of this study is to examine the ability of Curxanil 8/64WP (mixed fungicides between cymoxanil and mancozeb 8/64) in controlling Colletotrichum sp., and to know the resistance of the pathogen against fungicides in vitro. Field experiment was arranged in Complete Randomized Block Design with five treatments i. e. 0, 0.1, 0.2, 0.3, and 0.4% of each tested fungicide, compared with 0.2% mancozeb, with four replications. Fungicides toxicity were tested in vitro using Poisoned Food Technique. This experiment was arranged in Complete Randomized Design with eight treatments i.e. 0, 50, 100, 200, 800, 1000, 1500, 2000 ppm of mancozeb, cymoxanil, and curxanil with four replications. Fungicides resistance assay of Colletotrichum sp. against Curxanil was tested using the same method with gradually increasing fungicide concentrations.The results showed that in the field, anthracnose disease of red pepper can be controlled with 0.2% Curxanil. In vitro test showed that mancozeb at 800 ppm inhibited 98.8% colony diameter of Colletotrichum sp., while cymoxanil at 2000 ppm only reduced 37.2%. Colletotrichum sp. treated with gradually increasing concentration of Curxanil showed that its colony diameter could not be reduced and still grew 52.6% compared with one time treatment. This showed that Colletotrichum sp. had a potency to be resistant against cymoxanil. This problem can be avoided by mixing cymoxanil and mancozeb fungicides.